Czas Anny Frajlich - Tański, Paweł (Tematy i Konteksty, 2019)
Anna Frajlich has finally received a decent collection of critical studies concerning her diverse work. Born in 1942, a poet and prose writer, who has been living in the United States for years, should have received such a recognition a long time ago, as she is an intriguing artist and an important personality in the cultural life of Polish refugees. It was fortunate, therefore, that in 2018 th volume „Here I am / inhabit my own life.” Studies and sketches about the work of Anna Frajlich, edited by Wojciech Ligęza and Jolanta Pasterska was published in Kraków . The studies and sketches on the artistry of the author of Indian Summer were collected on 433 pages, the volume contains 31 papers, the collection is well composed. We have received a volume of excellent value that reads well, satisfying the hunger of intellectual curiosity and emotional greed for the voice of the American emigrant’s interpreters. That very important work perfectly fits in the literature on the subject of emigre literature, or in general – on the subject of Polish literature of the twentieth century and after 2000, bringing much needed studies on the writings of Anna Frajlich who is here and lives in our memory.